Test system creation for analysis of template switching effect during a reverse transcription in vitro - A. Y. Komkov; Y. B. Lebedev; V. I. Shvets (Тонкие химические технологии, 2011)
We investigated an in vitro system for the analysis of template switching effect of RNA-dependent DNA-polymerase during reverse transcription reaction. An RT-PCR-based approach was realized. An RNA sample was used as a template. The RNA contains a region with a stable secondary structure flanked by two homologous sequences. The described system can find use for testing overall performance of new and existing forms of the reverse transcriptase.